Penyuluhan Pola Hidup Sehat Cegah Komplikasi Hipertensi Di Desa Manunggang Jae Kecamatan Padangsidimpuan Tenggara - Hidayah, Arinil; Daulay, Nanda Masraini (Universitas Aufa Royhan Di Kota Padangsidipuan, 2020)
Hypertension is a non-communicable disease which is one of the main causes of premature death in the world. The world health organization (World Health Organization / WHO) estimates that currently the prevalence of hypertension globally is 22% of the total world population. Of the number of sufferers, only less than a fifth who make efforts to control their blood pressure. Hypertension is closely related to lifestyle and dietary factors. Lifestyle is very influential on the form of behavior or habits of a person that has a positive or negative influence on health. Lack of knowledge will also affect hypertensive patients to be able to overcome recurrences or take precautions so that complications do not occur. So based on the above problems, we intend to hold community service in the form of counseling on a healthy lifestyle to prevent complications of hypertension in community sufferers as an effort to prevent complications. The enthusiasm of the community is very good, and they feel the benefits of counseling by increasing their knowledge regarding the prevention of hypertension complications with a healthy lifestyle